A Framework for Process Reengineering in Higher Education: A case study of distance learning exam scheduling and distribution - Abdous, M'hammed; He, Wu (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
In this paper, we propose a conceptual and operational framework for process reengineering (PR) in higher education (HE) institutions. Using a case study aimed at streamlining exam scheduling and distribution in a distance learning (DL) unit, we outline a sequential and non-linear four-step framework designed to reengineer processes. The first two steps of this framework – initiating and analyzing – are used to initiate, document, and flowchart the process targeted for reengineering, and the last two steps – reengineering/ implementing and evaluating – are intended to prototype, implement, and evaluate the reengineered process. Our early involvement of all stakeholders, and our in-depth analysis and documentation of the existing process, allowed us to avoid the traditional pitfalls associated with business process reengineering (BPR). Consequently, the outcome of our case study indicates a streamlined and efficient process with a higher faculty satisfaction at substantial cost reduction.